2018
DOI: 10.31729/jnma.3654
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Herbal Mouthwash among Visually Impaired Residential School Students

Abstract: Introduction: Visually impaired patients are unable to visualize the plaque on tooth surfaces resulting in inadequate plaque removal and therefore the progression of dental caries and inflammatory disease of the periodontium. The objective of the study was to assess the effectiveness of herbal mouth wash in reduction of plaque and gingivitis among visually impaired children. Methods: Randomized controlled clinical trial was conducted with parallel groups study, comprising 6 to 20 year old visually impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
1
0
6
Order By: Relevance
“…In addition, there was also a problem of patients with visual impairment not being able to see a plaque on the tooth surface, resulting in inadequate plaque loss, development of dental caries, and periodontal inflammatory disease. (Dahal, Shrestha, and Bhagat 2018) In children with intellectual disabilities, the study results showed that other factors influencing the respondents' skills in cleaning dental plaque were the primary characteristics factors of children, excellent motor skills. (Sandy, Priyono, and Widyanti 2016) In an oral health status study conducted by Naveen et al with the target of children with intellectual disabilities, it was stated that 87.1% of children with disabilities (study group) had periodontal problems/conditions due to poor maintenance of oral hygiene.. (Katragadda, V, and Durga Mahendra 2021).…”
Section: Personal Cleanliness Problems In Children With Disabilitiesmentioning
confidence: 95%
“…In addition, there was also a problem of patients with visual impairment not being able to see a plaque on the tooth surface, resulting in inadequate plaque loss, development of dental caries, and periodontal inflammatory disease. (Dahal, Shrestha, and Bhagat 2018) In children with intellectual disabilities, the study results showed that other factors influencing the respondents' skills in cleaning dental plaque were the primary characteristics factors of children, excellent motor skills. (Sandy, Priyono, and Widyanti 2016) In an oral health status study conducted by Naveen et al with the target of children with intellectual disabilities, it was stated that 87.1% of children with disabilities (study group) had periodontal problems/conditions due to poor maintenance of oral hygiene.. (Katragadda, V, and Durga Mahendra 2021).…”
Section: Personal Cleanliness Problems In Children With Disabilitiesmentioning
confidence: 95%
“…Niños entre 5 y 12 años Dahal S, Shrestha A, Bhagat T. 2018 (27) Evaluar la efectividad del enjuague bucal a base de hierbas en la reducción de la placa y la gingivitis en niños con discapacidad visual…”
Section: Estudio Longitudinal De Intervenciónunclassified
“…Se demuestra que la técnica de BM es eficaz para mantener niveles de placa bacteriana bajos en personas con DV, es de resaltar que se debe realizar el seguimiento en la práctica de la técnica de cepillado debido a que se desconoce si después de terminados los estudios se continúa aplicando la misma. En cuanto a la edad de las personas involucradas en las intervenciones educativas, no se encontró ningún estudio realizado con adultos, la edad máxima que se reporta en los artículos es de 20 años (27) . Con respecto a las metodologías educativas para realizar una adecuada intervención en higiene bucal en niños y adolescentes con DV se requiere emplear diferentes métodos de entrada sensorial que han sido utilizados de forma variada en los estudios: braille (27,31,35,36) , audio-táctil-performance (ATP) (33,36) , braille y táctil (25) , braille y audio (24,26,29,34) y braille, audio y táctil (14,28,30,32) .…”
Section: Promoción Y Educación Para La Salud Bucalunclassified
See 2 more Smart Citations